The Effect of explicit vocabulary teaching on ESP students' vocabulary acquisition - a quasi-experimental research in Vung Tau Vocational Tourism College = hiệu quả của việc dạy từ vựng một cách rõ ràng, cụ thể đối với sự tiếp nhận từ vựng của sinh viên tiếng Anh chuyên ngành - Một nghiên cứu giả thực nghiệm tại trường Cao đẳng Nghề Du lịch Vũng Tàu). - Nguyễn, Thị Nhung (University of Languages and International studies, 2017)
M.A. Thesis English teaching methodology -- University of Languages and International studies. Vietnam National University, Hanoi, 2011